Synthesis and Characterization of Triazene and Thiourea Derivatives as Potential Antibacterial Agents - AINA SYAKIRAH, MOHAMMAD HUSSIN (Universiti Malaysia Sarawak, 2024)
Two different series of triazene 43a-i and thiourea derivatives 45a-i bearing acetanilide moiety with a total of 18 compounds have been successfully synthesized from 4’-aminoacetanilide as the core structure through azo coupling and nucleophilic substitution reaction, respectively. The structures were characterized by using Fourier-transform infrared (FTIR) spectroscopy, 1H and 13C nuclear magnetic resonance (NMR) analysis. The unexpected structural formation of 43a-i instead of the initially proposed azo derivatives 42a-i was confirmed by employing correlation spectroscopy (COSY). The antibacterial activity of 43a-i and 45a-i was tested against two types of bacteria which were Staphylococcus aureus (ATCC 25923), a Gram-positive bacterium and Escherichia coli (ATCC 25922), a Gram-negative bacterium. The antibacterial potential was utilized via turbidimetric kinetic method for 43a-i and Kirby-Bauer disc diffusion method for 45a-i. The study revealed that among the triazene series 43a-i, 43c bearing fluorine at para position was the most potent inhibitor against both bacteria with minimum inhibitory concentration (MIC) values of 68 ppm (S. aureus) and 84 ppm (E. coli), surpassing the standard ampicillin with the MIC values of 85 ppm (S. aureus) and 86 ppm (E. coli). The more nitrogen atoms on the triazene bridge along with the fluorine substituent were envisaged to promote greater hydrogen bond interactions with the bacterial receptors. On the other hand, another derivative of the 4’-aminoacetanilide called thiourea derivatives 45a-i showed susceptible inhibition against those bacteria, particularly 45a and 45f with 7-8 mm of inhibition zone, comparable to the standard ampicillin. The similar aspect these compounds possessed was the low molecular weight which resulted in better bacterial membrane penetration.